FENOMENA KOMUNIKASI ANGGOTA KOMUNITAS PARKOUR DI KOTA PEKANBARU SEBAGAI PELAKU OLAHRAGA EKSTRIM - Andri Wiranata; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Many forms of sport and community in the city of Pekanbaru be a new phenomenon. There are various forms of exercise there is, there is the sport that puts the health and some are put forward even to the level of extreme adrenalin. This study aims to investigate, Motif, Making of self and community members experience communication Parkour Flow It Pekanbaru as the perpetrators of extreme sports.This study uses qualitative research with phenomenological approach. Subjects consisted of 3 people informant in the city of Pekanbaru selected by using purposive. The study used data collection techniques in-depth interviews, observation, and documentation study. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed first, the motive extreme sports people Parkour in the city of Pekanbaru consists of motives for(Because Motive)the psychological impulse, sensation of its own and try. While the motive of hope (in order motive) which is to be practitioners of Parkour, the community recognized. Second, the meaning of which was given to him that is a self brave, self-independent, and self-recognized. Third, the communication experience categorized into two pleasant communication experience in the form of a good reception from family and friends and their support.and communication experience unpleasant form of satire and taunts from family and friends, the threat in the family as well as jeers and insults from the neighborhood.Keywords: Community Member Communications phenomenon Parkour in the city of Pekanbaru as Extreme Sports Performer